2022
DOI: 10.3390/f13111799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content and Preservatives on the Discoloration of Oil Palm (Elaeis guineensis Jacq.) Lumber

Abstract: Considering the current rate of expansion of the lumber processing industry in the world, the current annual allowable cut of one million cubic meters of round logs is considered to be insufficient to satisfy the increasing demand of timber industries. One major area that has been highlighted in the forest policy is the introduction of lesser-used species to widen the natural resource base of the forest and to address the imbalance between supply and demand for the resources. As a contribution to addressing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…The popularity of Dursban use among the younger adult population, those with secondary education, carpentry woodworkers, and woodworkers with over two years of experience could be linked purely to its effectiveness. For example, a study by Mensah et al (2022) clearly showed that Dursban is popular in Ghana and is effective as a chemical preservative for oil palm lumber. Although little evidence exists regarding these different choices and perceptions, it is interesting that about 57 % of the highly skilled building technology specialists did not see it as the most popular chemical option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of Dursban use among the younger adult population, those with secondary education, carpentry woodworkers, and woodworkers with over two years of experience could be linked purely to its effectiveness. For example, a study by Mensah et al (2022) clearly showed that Dursban is popular in Ghana and is effective as a chemical preservative for oil palm lumber. Although little evidence exists regarding these different choices and perceptions, it is interesting that about 57 % of the highly skilled building technology specialists did not see it as the most popular chemical option.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-point response scale to each item was modified and collapsed into a 3-point response scale category, namely, most popular (1), least popular (2), and unsure (3). This modification was necessary to meet the rule of the Chi-square test that contingency s with more than 1 degree of freedom expected count of a cell should not be less than 5 (Meyers et al, 2013).…”
Section: Data Analysis and Proceduresmentioning
confidence: 99%